A música performando a narrativa de "Inferninho" - Holanda, Caio Cardoso (Universidade Federal de São Carlos, 2025)
Ceará cinema is musically rich and often it's stories are touched by what the characters listen to and sing. In Inferninho (2018), by Guto Parente and Pedro Diógenes, musical performances are crucial to demarcate affections, positions and move the events of the plot. The story almost entirely happens in a bar with live music and explores a special and dreamlike universe. This research will analyze the ways in which the musical soundtrack adheres to the narrative of Inferninho, mainly through the songs performed by Luizianne (Samya De Lavor), which are mostly from forró, but sung in different versions and in several languages. The selection of the songs was made by the Ceará native Rita de Cássia, popularly known as "the greatest forró composer" in the country. Her songs and those of other exponents of the state populate the soundtrack, marking the strength of a specific cultural scene in recent film productions in the region. Sequences considered central will be meticulously analyzed in view of the central hypothesis of the research: that musical moments articulate in a very peculiar and creative way certain narrative axes through the relationship between popular musical genres and the bodies on stage.
The music performing the narrative of "My Own Private Hell"
Keywords: Trilha musical; Cinema cearense; Melodrama queer; Canção no cinema; Artifício; Soundtrack; Ceará cinema; Songs in cinema; Artifice; Queer melodrama; LINGUISTICA, LETRAS E ARTES::ARTES::CINEMA::INTERPRETACAO CINEMATOGRAFICA